Leukosit dan Kadar Bilirubin Total pada Ikterus Obstruktif yang Disebabkan oleh Tumor Pankreas - Liqva Nurul Fadhilah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Pancreatic cancer is a dangerous tumor which occurs protractedly and develops rapidly before showing its clinical symptoms. Initially, most of the patients with pancreatic cancer do not indicate specific symptoms thus, it leads to late diagnosis, and as a result, the patient had been in an advanced stage and this is one of the worst prognosis cancers. Objective To determine the correlation between leukocytes and total bilirubin levels in obstructive jaundice patients caused by pancreatic tumors an Abdul Muluk hospital in 2017-2019. Methods: Analytic descriptive with a cross-sectional approach was used in this present research. Total sampling was used as the sampling technique. The data regarding pancreatic tumor were obtained from secondary data with the results of medical recorded diagnosed with pancreatic tumors at Abdul Muluk hospital and was analyzed on a univariate basis to determine the distribution frequency and bivariate by using Spearman’s correlation test. The result of statistical analysis by using Spearman’s correlation test showed a p-value of 0,024 and 0,047 (p-value < 0,05) which means that there was a significant relationship between leukocytes and total bilirubin levels in obstructive jaundice patients that caused by pancreatic tumors at Abdul Moeloek hospital in 2017-2019. Conclusion There is a correlation between leukocytes and total bilirubin levels in obstructive jaundice patients caused by pancreatic tumors at Abdul Muluk hospital in 2017-2019.